Absence of the CHEK2 c.1100delC mutation in familial breast and ovarian cancer in Colombia: a case-control study (2018)
Background: BRCA1 and BRCA2 have been identified as high-penetrance breast cancer predisposition genes, but they only account for a small fraction of the inherited component of breast cancer. To explain the remaining cases, a polygenic model with a large number of low- to moderate-penetrance genes have been proposed; one of these, is the CHEK2 gene (Checkpoint Kinase 2). The objective of this study was to determine the role of the CHEK2 gene, specifically the c.1100delC mutation in familial breast cancer susceptibility in Colombian patients. Methods: We screened 131 high-risk breast and/or ovarian cancer patients (negative for mutations in BRCA1 and BRCA2) and 131 controls for the germline mutation CHEK2 c.1100delC by allele-specific PCR. Results: None of the cases or controls showed the CHEK2 c.1100delC mutation, neither as a homozygote nor as a heterozygote. Conclusions: Our results suggest that the CHEK2 c.1100delC mutation is not a risk factor for genetic susceptibility to familial breast or ovarian cancer in the Colombian population. The absence of the CHEK2 c.1100delC mutation in our population show the importance of considering ethnic background before offering a genetic test.